Candida albicans inactivation and cell membrane integrity damage by microwave irradiation - Campanha, Nara Hellen; Pavarina, Ana Claudia [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Vergani, Carlos Eduardo [UNESP]; Machado, Ana Lucia [UNESP]; Spolidório, Denise Madalena Palomari [UNESP] (Wiley, 2007)
In indicating the microwave irradiation for disinfecting dentures it is necessary to see how this procedure influences Candida albicans integrity and viability. The aim of this study was to evaluate the ability of microwaves to inactivate C. albicans and damage cell membrane integrity. Two 200-ml C. albicans (ATCC 10231) suspensions were obtained. A sterile denture was placed in a beaker containing the Experimental (ES) or the Control suspension (CS). ES was microwaved at 650 W for 6 min. Suspensions were optically counted using methylene blue dye uptake as indicative of membrane-damaged cells; spread on Agar Sabouraud dextrose (ASD) for viability assay; or spectrophotometrically measured at 550 nm. Cell-free solutions were submitted to content analyses of protein (Bradford and Pyrogallol red methods); Ca++ (Cresolftaleine complexone method); DNA (spectrophotometer measurements at 260 nm) and K + (selective electrode technique). Data were analysed by Student's t- or Wilcoxon z-tests (α = 0.05). All ES cells demonstrated cell membrane damage. Viable cells were non-existent in the ES ASD plates. No significant difference in optical density between ES and CS was observed (P = 0.272). ES cells released significantly high protein (P < 0.001, Bradford; P = 0.005, Pyrogallol red), K+ (P < 0.001), Ca++ (P = 0.012) and DNA (P = 0.046) contents. Microwaves inactivated C. albicans and damaged cell membrane integrity. © 2007 The Authors.
Keywords: Candida albicans; Complete; Denture; Denture stomatitis; Disinfection; Microwaves; Yeast; calcium; DNA; methylene blue; potassium ion; agar medium; cell free system; cell membrane; cell viability; content analysis; controlled study; denture; DNA content; DNA determination; electrode; membrane damage; microwave irradiation; nonhuman; optical density; priority journal; protein analysis; rank sum test; spectrophotometer; spectrophotometry; Student t test; suspension; Calcium; Cell Membrane; Colony Count, Microbial; DNA, Fungal; Fungal Proteins; Methylene Blue; Microbial Viability; Permeability; Potassium; Spectrophotometry